Multi-DFIGs Aggregated Model based SSCI Analysis - Hua Li, Chaohang Zheng (International Journal of Advanced Science and Technology, 2020)
In the wind farm, a large number of wind turbines operate at the same time. The operating parameters of these wind turbines not only affect their own stability, but also affect the stability of other wind turbines. Firstly, a second-order circuit with two branches is established and analyzed. Theoretical analysis shows that when there are differences between the two branches, it will affect the system's original system subsynchronous oscillation. Secondly, the equivalent analysis of the doubly-fed induction generator(DFIG) is carried out by impedance method, and the influence factors of wind speed, the parameters of rotor side converter(RSC) on the equivalent impedance of the system is studied. Finally, combined with the results obtained by the theory, the simulation shows that after sub-synchronous control interaction(SSCI) phenomenon occurs in one DFIG of a certain node, this phenomenon can be changed by changing the operating parameters of other DFIGs connected to the same node. Therefore, SSCI of the system is closely related to the DFIGs with different operating parameters.